Polyvinylbutyral‐assisted synthesis and characterization of SnS mesoporous fibers via electrospinning process. Issue 33 (20th May 2015) - Hsu, Kuo‐Chin; Wu, Dong‐Yang; Lin, Pei‐Ying; Fu, Yaw‐Shyan; Liao, Jiuun‐Der
ABSTRACT Tin sulfide (SnS) has the potential to be used as a low‐cost absorber material for applications in thin film photovoltaic solar cells. In this study, polyvinylbutyral/SnS (PVB/SnS) composite fibers were synthesized through a relatively simple electrospinning process. SnS mesoporous fibers were obtained from PVB/SnS composite fibers after sintering treatment at 500°C for 1 h in N2 atmosphere. The SnS mesoporous fibers were then characterized using X‐ray powder diffraction, scanning electron microscopy, thermogravimetric analysis, and transmission electron microscopy. The optical properties of SnS mesoporous fibers were also recorded by UV–vis absorption spectroscopy. The results showed that the synthesized SnS mesoporous fibers exhibited a single phase, stoichiometric composition, with good crystallinity, a size ranging from 100 to 200 nm, and a band gap of 1.49 eV. The as‐prepared SnS mesoporous fibers are thus a suitable material to achieve visible light absorption in a thin film solar cell. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42388.